2008
DOI: 10.1071/ah080415
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in hospitalisation following pulmonary rehabilitation in patients with COPD

Abstract: Objectives: Pulmonary rehabilitation (PR) improves exercise capacity and health-related quality of life (HRQoL), and reduces health care utilisation. This study quantified outcomes of a PR program over a 6-year period and determined the effects of PR on hospitalisation. Methods:Patients with chronic obstructive pulmonary disesae (COPD) who entered an 8-week outpatient PR program from 1998 to 2003 were included. Functional exercise capacity (6-minute walk distance [6MWD]) and HRQoL (Chronic Respiratory Disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
65
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 26 publications
2
65
0
Order By: Relevance
“…This outcome would likely result in a reduction in health care costs, which is consistent with the findings of other studies [18][19][20]. In one such study by Raskin and colleagues, 128 patients received PR at 11 outpatient centers, and there were 0.25 fewer hospitalizations in the year following PR [21].…”
Section: Discussionsupporting
confidence: 78%
“…This outcome would likely result in a reduction in health care costs, which is consistent with the findings of other studies [18][19][20]. In one such study by Raskin and colleagues, 128 patients received PR at 11 outpatient centers, and there were 0.25 fewer hospitalizations in the year following PR [21].…”
Section: Discussionsupporting
confidence: 78%
“…The study had a low drop-out rate of 9%, which is in contrast with higher attrition from clinical pulmonary rehabilitation programmes [2]. One reason for this difference may be that ''drop out'' from a clinical pulmonary rehabilitation programme is often reported when patients do not attend training, whereas, in a clinical trial, participants remain in the trial as long as some of the final assessments are performed (i.e.…”
Section: Discussionmentioning
confidence: 70%
“…Pulmonary rehabilitation has been shown to improve health-related quality of life (HRQoL) [1] and exercise capacity, as well as reduce hospital admissions and length of stay in people with chronic obstructive pulmonary disease (COPD) [2][3][4]. Globally, the demand for pulmonary rehabilitation far outweighs the availability of programmes [5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Using a similar population group (mean age 68 years, FEV1 44% predicted), a study in 10 centres in California reported significant improvement, although the benefits regressed over an 18-month followup [10]. An Australian study with 187 patients also showed improvements in 6MWD and HRQL following PR and reported a 46% reduction in the number of patients admitted to hospital with an exacerbation and a 62% reduction in total bed days following PR [22]. Griffiths et al reported in 200 patients, mainly with COPD.…”
Section: Discussionmentioning
confidence: 97%